Bentuk Penegakan Ham di Indonesia Sebagai Negara Hukum - Nurazita, Raja Novenia Ahza; C, Cherline; Putri, Nursari Ramadhila (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Human Rights are the rights that every human being on earth has a creatures created by God. The enforcement and protection of human rights is a reflection of the Pancasila principle contained in the second Pancasila, namely just and civilized humanity. This sentence explains that every creature on this earth must be treated fairly regardless of anything because this is their right. A concept of the rule of law is a concept which is universal in nature and is adhered to by almost all countries in the world. There are two types, namely the first is the Rechsstaat legal state and The Rule of Law. These two types have characteristics and similarities, namely those related to the protection of human rights. How to overcome things that occur as a result of violations of human rights, namely by establishing a National Human Rights Commission and a Human Rights Court, which is progress in the enforcement and court of human rights.